EMPLOYEE OWNERSHIP AS DRIVER OF THE NEED FOR CHANGE IN ORGANIZATIONS - Talebi, Safoora (European Scientific Journal, ESJ, 2015)
Management of change in an organization is interested in the employment of strategies that will be prompt and effective in overcoming resistance to change. Change relies on the level of commitment from the members of an organization. Therefore, this article is an evaluation of the influence that employee ownership has on the change process of an organization. In particular, this article explores how employee ownership of an organization influences the change process by determining the level of commitment that the employees will demonstrate when they realize the need for change inevitably affects them. Thisarticle employs a qualitative analysis of relevant literature from past studies that haveexplored the many dimensions of commitment that correlate with change. The article found out that allowing employees to be part owners of a company that is strategizing a turnaround reinforces the employees’ internalization of commitment, which speeds up the process of organizational change. Notably, the employees’ goals synchronize with the organization’s goals to create a mutual benefits relationship. However, this article does not explain the reasons that made some employees leave their organizations after even owning organizations as indicated by several studies. Nonetheless, this article’s topic is insightful by uncovering the underlying motivations that drive employees in embracing or resisting organizational change. Practically, findings from this article help stakeholders in incorporating employee ownership or related concepts in making employees realize the need for change. Employees who are part owners of an organization realize that their welfare is dependent on the performance of their organization.